2014
DOI: 10.1016/j.jelekin.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Co-activation of upper limb muscles during reaching in post-stroke subjects: An analysis of the contralesional and ipsilesional limbs

Abstract: The purpose of this study was to analyze the change in antagonist co-activation ratio of upper-limb muscle pairs, during the reaching movement, of both ipsilesional and contralesional limbs of post-stroke subjects. Nine healthy and nine post-stroke subjects were instructed to reach and grasp a target, placed in the sagittal and scapular planes of movement. Surface EMG was recorded from postural control and movement related muscles. Reaching movement was divided in two sub-phases, according to proximal postural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…The mean time since the stroke episode was 6.18 ± 3.12 years. Regarding the type of stroke, 38.10% (8) were ischemic and 61.90% (13) were hemorrhagic. The mean score of participants on the motor function domain of the UL-FMA was 26.87 out of 66 points (SD 10.6), with 72.25 out of 126 points (SD 20.41) on the total score of the UL-FMA (including the sensory, passive ROM, and pain subscales).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean time since the stroke episode was 6.18 ± 3.12 years. Regarding the type of stroke, 38.10% (8) were ischemic and 61.90% (13) were hemorrhagic. The mean score of participants on the motor function domain of the UL-FMA was 26.87 out of 66 points (SD 10.6), with 72.25 out of 126 points (SD 20.41) on the total score of the UL-FMA (including the sensory, passive ROM, and pain subscales).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the UL muscles involved in reaching movements, a deficit in muscle control and activation has been observed (5, 12, 13). The synergistic contraction of the shoulder flexor and extensor muscles during reach becomes deteriorated due to muscle weakness and; therefore, the resulting movement is deficient (14).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have reported that increased agonist/antagonist co-activation of biceps/triceps about the elbow joint impedes reaching movement however did not measure biceps co-activation with deltoid (Silva et al, 2014). Substantial co-activation at the elbow joint was observed in the present study however it began prior to the onset of elbow extension movement during the lifting portion of the task.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that spastic co-contraction may contribute to limitations in active movement (4). However, to date, the impact of this disabling form of muscle overactivity on motor function in brain-injured adults has been only sparsely and indirectly studied (5). In addition, most treatments aimed at improving upper limb function, such as rehabilitation or botulinum toxin, focus on spasticity as the primary outcome in clinical practice (6).…”
mentioning
confidence: 99%